Unlocking the Power of Pre-Reading: Strategies for Better Comprehension and Engagement - A’thi Fauzani Wisudawati; Rizka Maulina Wulandari; Muhammad Isa; Ita Permatasari; Muhyiddin Aziz; Imam Mudhofir (Jurnal Pendidikan dan Sastra Inggris, 2025)
This study aims to analyze the implementation of pre-reading activities in the Intermediate Reading classroom and their impact on students’ comprehension and engagement. The respondents consisted of 55 students from the English Department who participated in the study. Data were gathered through questionnaires and descriptive analysis of classroom practices to identify the types, purposes, and effects of pre-reading strategies used by lecturers. The findings reveal that lecturers employ a variety of pre-reading techniques such as vocabulary introduction, topic discussion, brainstorming, and content prediction to activate students’ prior knowledge and prepare them for the reading process. These strategies are carried out through interactive activities including word games, group discussions, visual media presentation, and short pre-reading quizzes. Such activities not only create a dynamic learning environment but also help students anticipate the content of the text and establish connections between their background knowledge and new information. The results indicate that pre-reading activities significantly contribute to enhancing text comprehension, increasing motivation, and promoting active student participation during reading sessions. Consequently, pre-reading is viewed not merely as an introductory stage but as an essential pedagogical approach that fosters engagement, comprehension, and critical thinking in EFL reading instruction, leading to more effective and meaningful reading experiences for learners.